2010
DOI: 10.1038/ncb2030
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 Thr 45 phosphorylation is a replication-associated post-translational modification in S. cerevisiae

Abstract: Post-translational histone modifications are crucial for the regulation of numerous DNA-templated processes, and are thought to mediate both alteration of chromatin dynamics and recruitment of effector proteins to specific regions of the genome 1 . In particular, histone Ser/Thr phosphorylation regulates multiple nuclear functions in the budding yeast Saccharomyces cerevisiae, including transcription, DNA damage repair, mitosis, apoptosis and sporulation 2 . Although modifications to chromatin during replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 32 publications
3
86
0
Order By: Relevance
“…Thr45 has also been reported to be phosphorylated in budding yeast by the kinase Cdc7-Dbf4. This modification has been related to proper replication of DNA in budding yeast (5). Another significant C-terminal modification is H3 Tyr41 phosphorylation.…”
Section: Histone H3mentioning
confidence: 99%
“…Thr45 has also been reported to be phosphorylated in budding yeast by the kinase Cdc7-Dbf4. This modification has been related to proper replication of DNA in budding yeast (5). Another significant C-terminal modification is H3 Tyr41 phosphorylation.…”
Section: Histone H3mentioning
confidence: 99%
“…Histone H3-S28ph is linked to H3-S10ph and is associated with transcriptional response to stress in mammalian cells (Clayton and Mahadevan 2003;. Histone H3-T45ph functions during DNA replication (Baker et al 2010), and, lastly, H2A-S121ph has a role in DNA damage and protection of centromeric cohesion in budding yeast (Fernius and Hardwick 2007;Moore et al 2007). …”
Section: Does Rts1 Suppression Require Specific Histone Residues?mentioning
confidence: 99%
“…Phosphorylation of H3 Thr45 is mediated by the kinase Cdc7-Dbf4. It has been shown that Thr45 phosphorylation peaks during DNA replication and that the loss of this phosphorylation site causes phenotypes consistent with replicative defects (Baker et al, 2010).  Topoisomerase Top2 cleavage and re-sealing of the phosphodiester backbone is required for replication and recombination processes.…”
Section: Post-translational Modificationsmentioning
confidence: 99%